Public-key cryptography – PKC 2017. 20th IACR International Conference on Practice and Theory in Public-Key Cryptography, Amsterdam, the Netherlands, March 28-31, 2017, Proceedings /: 20th IACR International Conference on Practice and Theory in Public-Key Cryptography, Amsterdam, the Netherlands, March 28-31, 2017, Proceedings. Part I : (2017) - Unknown
No abstract available